2018
DOI: 10.1557/mrs.2018.31
|View full text |Cite
|
Sign up to set email alerts
|

Dual-stimulus magnetoelectric energy harvesting

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Magnetoelectric composites with large nonzero α E in the absence of a DC magnetic field, namely with a "self-biased ME effect," have been developed in various configurations using different strategies. 28 These self-biased ME composites are discussed in the article by Chu et al in this issue, 29 and their use for energy harvesting is illustrated. Further, using these ME composites, dual-mode energy harvesting can be accomplished, where both magnetic field and vibration can be simultaneously converted into electricity.…”
Section: Energy Harvesting From Mechanical Vibrations and Magnetic Fimentioning
confidence: 99%
See 2 more Smart Citations
“…Magnetoelectric composites with large nonzero α E in the absence of a DC magnetic field, namely with a "self-biased ME effect," have been developed in various configurations using different strategies. 28 These self-biased ME composites are discussed in the article by Chu et al in this issue, 29 and their use for energy harvesting is illustrated. Further, using these ME composites, dual-mode energy harvesting can be accomplished, where both magnetic field and vibration can be simultaneously converted into electricity.…”
Section: Energy Harvesting From Mechanical Vibrations and Magnetic Fimentioning
confidence: 99%
“…Chu et al highlight the key materials and requirements for the magnetovibration dual-mode energy harvesting. 29 Research has demonstrated high power densities under resonance condition using oriented single-crystal fiber-composite-based ME laminates.…”
Section: Energy Harvesting From Mechanical Vibrations and Magnetic Fimentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9] Search-coil, as a conventional magnetic sensor, has a high magnetic sensitivity, and its detectable magnetic field is as low as 20 fT/Hz 1/2 at 1 kHz. [16][17][18][19][20][21][22][23] Compared with magnetic sensors mentioned above, the ME sensor shows great potential for weak magnetic detection due to its superhigh magnetic field sensitivity. And the search-coil is often limited to the detection for the alternating current magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…A fluxgate www.advmattechnol.de working at room-temperature and on the basis of the strainmediated magneto-to-electric coupling principle, have emerged recently. [16][17][18][19][20][21][22][23] Compared with magnetic sensors mentioned above, the ME sensor shows great potential for weak magnetic detection due to its superhigh magnetic field sensitivity. It also has the advantages of low cost, light weight, easy fabrication, and high magnetic directivity.…”
Section: Introductionmentioning
confidence: 99%